Silent Way: Metode Pembelajaran Bahasa Arab yang Mendorong Peserta Didik Lebih Kreatif, Mandiri, dan Bertanggung Jawab - Junanah Junanah (EL-TARBAWI, 2014)
One of the distresses that students ever deal with in learning language is they are too forced by the way teachers give the lesson or the methods they use. As a result, the students have no chances to demonstrate their creativity in mastering foreign language. One of language teaching methods called Silent Way states one of the basic principles is “teaching should be subordinated to learning”. In the other words, to teach means to serve the learning rather than dominate it. Learning is a process which which we initiate by ourselves by mobilizing our inner resource (perception, awareness, cognition, imagination, intuition, creativity, etc.) to meet the challenge at hand. Learners should develop independence, autonomy and responsibility. At the same time, learners have to corporate with each other in the process of solving language problems as taught by this method. This method has widely used in teaching many language such as English, French, Spanish, Hindi, Arabic and more. In Arabic this method then called al- thariqah al-shamitah. In the situation that learning Arabic to stagnate, the method could be the best choice to apply.